Approaches Involved in the Vegetable Crops Salt Stress Tolerance Improvement: Present Status and Way Ahead - Behera, Tusar Kanti; Krishna, Ram; Ansari, Waquar Akhter; Aamir, Mohd; Kumar, Pradeep; Kashyap, Sarvesh Pratap; Pandey, Sudhakar; Kole, Chittaranjan (Frontiers in Plant Science, 2022)
Salt stress is one of the most important abiotic stresses as it persists throughout the plant life cycle. The productivity of crops is prominently affected by soil salinization due to faulty agricultural practices, increasing human activities, and natural processes. Approximately 10% of the total land area (950 Mha) and 50% of the total irrigated area (230 Mha) in the world are under salt stress. As a consequence, an annual loss of 12 billion US is estimated because of reduction in agriculture production inflicted by salt stress. The severity of salt stress will increase in the upcoming years with the increasing world population, and hence the forced use of poor-quality soil and irrigation water. Unfortunately, majority of the vegetable crops, such as bean, carrot, celery, eggplant, lettuce, muskmelon, okra, pea, pepper, potato, spinach, and tomato, have very low salinity threshold (ECt, which ranged from 1 to 2.5 dS m–1 in saturated soil). These crops used almost every part of the world and lakes’ novel salt tolerance gene within their gene pool. Salt stress severely affects the yield and quality of these crops. To resolve this issue, novel genes governing salt tolerance under extreme salt stress were identified and transferred to the vegetable crops. The vegetable improvement for salt tolerance will require not only the yield influencing trait but also target those characters or traits that directly influence the salt stress to the crop developmental stage. Genetic engineering and grafting is the potential tool which can improve salt tolerance in vegetable crop regardless of species barriers. In the present review, an updated detail of the various physio-biochemical and molecular aspects involved in salt stress have been explored.